(untitled) (Asian Journal of Current Engineering and Maths, 2013)
A sequence of independent lifetimes X1,......, Xm, Xm+1,......, Xn were observed from two-parameter Weibull distribution with probability density function f(x, Â but later it was found that there was a change in the system at some point of time m and it is reflected in the sequence after Xm by change probability mass function f(x, .The Bayes estimators of m , Â are derived. The effects of correct and wrong prior information on the Bayes estimates are studied.